2019
DOI: 10.1055/s-0039-1697591
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal and Hepatobiliary Disease in Cystic Fibrosis

Abstract: Cystic fibrosis (CF) is a multiorgan disease, and gastrointestinal (GI) manifestations can contribute to significant morbidity and mortality for individuals with CF. Up to 85% of patients with CF experience GI symptoms, thus addressing the GI aspects of this disease is paramount. With the advent of highly effective CF transmembrane conductance regulator modulators that are increasingly available, many individuals with CF now have significantly improved life expectancy. With these advances, GI manifestations th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 188 publications
(270 reference statements)
0
10
0
Order By: Relevance
“…CF patients are able to live well into their sixth decade of life [ 24 , 25 ]. In that context, abdominal complications [ 26 ], including hepatic, pancreatic and gastrointestinal malignancy [ 27 30 ], are increasing. Monitoring of abdominal complications of CF [ 31 ] could be improved with native MRI diagnostics, including DWI [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…CF patients are able to live well into their sixth decade of life [ 24 , 25 ]. In that context, abdominal complications [ 26 ], including hepatic, pancreatic and gastrointestinal malignancy [ 27 30 ], are increasing. Monitoring of abdominal complications of CF [ 31 ] could be improved with native MRI diagnostics, including DWI [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic insufficiency typically occurs in the "classic, typical, or severe" phenotype. 38 Although this condition was present in 69.1% of our patients, there was no correlation with atelectasis. 4,[21][22][23] A published article indicated that the formation of pulmonary atelectasis was related to acute pancreatitis, although not in patients with CF.…”
Section: Discussionmentioning
confidence: 49%
“…Clinical symptoms of pancreatic insufficiency include greasy Introductory Chapter: Basics of Cystic Fibrosis DOI: http://dx.doi.org/10.5772/intechopen.97537 stools, flatulence, abdominal bloating, and poor weight gain. The CF liver disease is characterized by the hyper-viscous bile causing obstructive cholangitis initially leading to focal biliary fibrosis and subsequently to biliary multinodular cirrhosis and portal hypertension [17]. Gastrointestinal manifestations of CF occur due to pancreatic insufficiency, thickened intestinal secretions, undigested food remnants, poor motility, and fecal stasis with resultant impaction of mucofeculent material in the distal ileum and right colon presented as meconium ileus in the newborn and distal intestinal obstruction syndrome in the post-neonatal life.…”
Section: Clinical Picture Of Cystic Fibrosismentioning
confidence: 99%